The rights of refugees under international law / James C. Hathaway. - Hathaway, James C. (Cambridge University Press, 2021)
Do states have a duty to assimilate refugees to their own citizens? Are refugees entitled to freedom of movement, to be allowed to work, to have access to public welfare programs, or to be reunited with family members? Indeed, is there even a duty to admit refugees at all? This fundamentally rewritten second edition of the award-winning treatise presents the only comprehensive analysis of the human rights of refugees set by the UN Refugee Convention and international human rights law. It follows the refugee's journey from flight to solution, examining every rights issue both historically and by reference to the decisions of senior courts from around the world. Nor is this a purely doctrinal book: Hathaway's incisive legal analysis is tested against and applied to hundreds of protection challenges around the world, ensuring the relevance of this book's analysis to responding to the hard facts of refugee life on the ground.